Ágnes Heller and Hannah Arendt : a dialogue - Prior, Ángel; Rivero, Ángel (Cambridge Scholars Publishing, 2018)
This book reconstructs, through texts by Ágnes Heller and international scholars, a timely conversation between Hannah Arendt and Heller on the malaises of modernity. This valuable work will be appreciated both by academics and students interested in social and political philosophy, in addition to the wider public curious of intellectual history. Both Arendt and Heller are great thinkers with the ability to enlighten the great moral and political problems of our time. Although these two great figures belong to different generations, the dialogue reconstructed here provides a fuller picture of.